Acceleration and the Dilemma of Deceleration in Late Modern Societies: ترجمة نص لـ"هارتموت روزا": التسارع ومعضلة التباطؤ في المجتمعات الحداثية المتأخرة - Maafa , Hichem (Maalim, 2026)
The purpose of this article is to translate the text "Acceleration and the Dilemma of Deceleration in Late Modern Societies" by the German sociologist and philosopher Hartmut Rosa. In it, Rosa analyzes the complex relationship between acceleration and deceleration within the temporal structures of late modern societies. Rosa identifies the most significant paradox characterizing late modernity: while the latter is governed by processes of accelerating social change, it simultaneously produces numerous forms of deceleration, most notably intentional or ideological deceleration, which acts as a counter-movement to acceleration. However, through this text, Rosa argues that deceleration in all its forms is not an independent counter-force, but rather a remnant or direct consequence of acceleration processes. Thus, "acceleration" becomes a comprehensive concept permeating all aspects of late modern societies, transforming our relationship to the world as such. Rosa concludes his analysis of this tense relationship between the two concepts by stating that understanding modernity is only possible by analyzing the structural tension between the dynamics of acceleration and the forces of cultural and structural slowdown.